Pengaruh Tingkat Kesadaran Wajib Pajak, Sanksi Pajak dan Penerapan Self Assessment System terhadap Kepatuhan Pelaporan SPT Tahunan Wajib Pajak UMKM Orang Pribadi - Onny, Alifah Maharanie Putri; Andrian, Andrian (UNIVERSITAS KALBIS, 2025)
This study was conducted with the aim of analyzing the effect of taxpayer awareness, tax sanctions, and the application of self-assessment on individual taxpayer compliance at KPP Pratama Pulogadung. This research method uses a quantitative approach and data is collected using primary data, the sample collection technique uses purposive sampling with a questionnaire of 150 respondents, the population in this study were all individual taxpayers at KPP Pratama Pulogadung. Hypothesis testing to test each variable is done with validity tests, reliability tests, classicalassumption tests, multiple linear regression analysis tests. F-test and t-test using the SPSS 26 program. The results of this study indicate that taxpayer awareness and self-assessment has a positive effect on taxpayer compliance. Meanwhile, tax sanctions have a negative effect on taxpayer compliance. Furthermore, taxpayer awareness, tax sanctions, and the use of self-assessment can simultaneously influence taxpayer compliance.